Effect of Online Training on the Reliability of Assessing Sacroiliac Joint Radiographs in Axial Spondyloarthritis: A Randomized, Controlled Study - Hadsbjerg, Anna E F; Østergaard, Mikkel; Paschke, Joel; Micheroli, Raphael; Pedersen, Susanne J; Ciurea, Adrian; Nissen, Michael J; Bubova, Kristyna; Wichuk, Stephanie; de Hooge, Manouk; Krabbe, Simon; Mathew, Ashish J; et al. (The Journal of rheumatology, 2024)
OBJECTIVE: Radiographic assessment of sacroiliac joints (SIJs) according to the modified New York (mNY) criteria is key in the classification of axial spondyloarthritis but has moderate interreader agreement. We aimed to investigate the improvements of the reliability in scoring SIJ radiographs after applying an online real-time iterative calibration (RETIC) module, in addition to a slideshow and video alone. METHODS: Nineteen readers, randomized to 2 groups (A or B), completed 3 calibration steps: (1) review of manuscripts, (2) review of slideshow and video with group A completing RETIC, and (3) re-review of slideshow and video with group B completing RETIC. The RETIC module gave instant feedback on readers' gradings and continued until predefined reliability ([Formula: see text]) targets for mNY positivity/negativity were met. Each step was followed by scoring different batches of 25 radiographs (exercises I to III). Agreement ([Formula: see text]) with an expert radiologist was assessed for mNY positivity/negativity and individual lesions. Improvements by training strategies were tested by linear mixed models. RESULTS: In exercises I, II, and III, mNY [Formula: see text] were 0.61, 0.76, and 0.84, respectively, in group A; and 0.70, 0.68, and 0.86, respectively, in group B (ie, increasing, mainly after RETIC completion). Improvements were observed for grading both mNY positivity/negativity and individual pathologies, both in experienced and, particularly, inexperienced readers. Completion of the RETIC module in addition to the slideshow and video caused a significant [Formula: see text] increase of 0.17 (95% CI 0.07-0.27; P = 0.002) for mNY-positive and mNY-negative grading, whereas completion of the slideshow and video alone did not ([Formula: see text] = 0.00, 95% CI -0.10 to 0.10; P = 0.99). CONCLUSION: Agreement on scoring radiographs according to the mNY criteria significantly improved when adding an online RETIC module, but not by slideshow and video alone.
Keywords: diagnostic imaging; Humans; Radiography; Sacroiliac Joint; education research; radiografie; spondyloarthritis; axiální spondyloartritida; Female; lidé; reprodukovatelnost výsledků; ženské pohlaví; Male; Reproducibility of Results; Axial Spondyloarthritis; radiography; medical education; odchylka pozorovatele; Observer Variation; sakroiliakální kloub; mužské pohlaví; radiology